Progress against poverty : sustaining Mexico's Progresa-Oportunidades program - Levy, Santiago (Brookings Institution Press, 2006)
"Case study of Progresa-Oportunidades that describes the origins, objectives, and institutional design and scope of Progresa; provides a broad assessment of results to date; discusses the main challenges faced by the program in the future; and makes some suggestions for poverty programs drawn from the main lessons of the study"--Provided by publisher